Which Protective Factors Are Associated with the Mental Health of Syrian Students in Germany? A Register-Based Cross-Sectional Study - Hosari, Remy Rahim; Borho, Andrea; Morawa, Eva; Erim, Yesim (International Journal of Environmental Research and Public Health, 2022)
The aim of this online, register-based cross-sectional study was to investigate the frequency of psychological distress and protective factors among 136 Syrian students in Germany. The survey measured depression and anxiety (Patient Health Questionnaire-4), post-traumatic stress (Impact of Event-Scale-6), as well as resources social support (ENRICHD Social Support Instrument), optimism (Optimism–Pessimism-2 Scale) and religiosity (Duke Religion Index). A total of 26.50% of the sample were female. A total of 38.93% met criteria for clinically relevant depressive respectively generalized anxiety symptoms and 15.72% showed prominent PTSD scores. Participants screened positive for mental distress reported significantly less social support (p = 0.001) and less optimism (p = 0.002) than participants without mental distress. In multiple regression analyses, higher levels of feeling welcome in Germany, social support and intrinsic religiosity were significantly associated with lower levels of depression and generalized anxiety. Significant associations with lower PTSD levels were found with higher levels of social support and optimism. The results show that Syrian students in Germany are more psychologically burdened compared to other Syrian refugee samples, except for PTSD. This suggests that besides the stress caused by flight and trauma, stressors such as studying and social isolation could be considered as additional impediments for mental health and require intervention measures.
CRIS-Team Scopus Importer:2022-12-23
Keywords: depression; generalized anxiety disorder; mental health; post-traumatic stress disorder; protective factors; Syrian students; university